Geotechnical Properties of Lateritic Soil Stabilized with Cement and Corn Cob Ash - Dukup, Meshak. Yunana; Matawal, D. S.; Umar, S.Y; Salaudeen, A (Journal of Multidisciplinary Research Advancements, 2026)
This study investigates the stabilization of laterite soil with blends of cement and corn cob ash (CCA) at different percentages. Lateritic soil contains a significant amount of clay materials; its strength and stability cannot be assured under load especially in the presence of moisture. The presence of high plastic clay in lateritic soil causes soil cracks and damage on road pavements, road ways, building foundations, or any civil engineering construction projects. Due to deficiencies in properties of laterite soil for highway construction, there’s need to improve its properties through stabilization process. This study examines the stabilization of laterite soil using a mixture of corn cob ash (CCA) and cement at different percentages. A central composite design (CCD) was employed to optimize the mixture proportions of CCA and cement and the responses were unconfined compressive strength, (UCS) and California bearing ratio (CBR). The result of natural soil had an average value of the liquid limit, plastic limit and plasticity index as 22.7, 6.5 and 16.2 respectively, while the linear shrinkage was 11%. The results of the numerical optimization revealed that the optimal mixture consisted of 2% CCA, 3% Cement, 82.9% CBR Unsoaked, 31.2% CBR Soaked, 352 N/mm2 UCS at 7 days, 357 N/mm2 UCS at 7+7 days, 419.1 N/mm2 UCS at 14 days and 795.9 N/mm2 UCS at 28 days. The stabilized soil samples exhibited significant improvements in unconfined compressive strength, durability, and reduced plasticity. The use of CCA as a supplementary cementitious material also offers environmental benefits by reducing waste and promoting sustainable construction practices. The findings of this study demonstrate the potential of CCA and cement stabilization for improving soil properties and provide valuable insights for future applications in geotechnical engineering.